ANALISIS SWOT DAYA DUKUNG DAERAH TERHADAP PENGEMBANGAN KAWASAN INDUSTRI KABUPATEN BLITAR - Khuzaini Khuzaini; Suwitho Suwitho (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2007)
The first step of industrial area development needs to find out the current conditional supportiveness in the smallest area unit. The smallest unit of Regency or Municipality is subdistrict. The setting of this study is Blitar Regency while its smallest area units studied are the Subdistricts of Bakung, Wonotirto, Sutojayan, Panggungrejo, Wates, Binangun, Kesamben, Selorejo, Doko, Wlingi, Talun, Selopuro, Kanigoro, Kademangan, Sanankulon, Srengat, Udanawu, Wonodadi, Ponggok, Nglegok, Garum and Gandusari.. The method used is SWOT analysis which considers internal factor constructed in IFAS (Internal Strategic Factor Analysis Summary) table and external factor constructed in EFAS (External Strategic Factor Analysis Summary) table. The highest IFAS values is Subdistrict Ponggok, while the highest EFAS values is Kademangan. Based on IFAS and EFAS values, the quadrant position will be derived in SWOT matrix whose x axis is IFAS and y axis is EFAS. There are four quadrants in SWOT matrix, they are S-O (Strengths – Opportunities), W-O (Weakness-Opportunities), S-T (Strengths-Threats), and W-T (Weakness-Threats). The results of this current study suggest that from 22 Subdistricts we studied, there are ten Subdistricts in S-O quadrant, two in W-O quadrant, five in S-T quadrant and five in W-T quadrant. Based on the position of these Subdistricts in SWOT quadrant, the appropriate strategy for each Subdistrict in developing their area in order to support the development of industrial area will be determined.